Human epidermal growth factor receptor 2/neu overexpression in urothelial carcinoma of the bladder and its prognostic significance: Is it worth hype? - Kumar, Santosh; Prajapati, Omprakash; Vaiphei, Kim; Parmar, Kalpesh Mahesh; Sriharsha, A. S.; Singh, S.K (South Asian journal of cancer, 2015)
Abstract Aims: In urothelial tumors of the urinary bladder, human epidermal growth factor receptor 2 (HER-2)/neu expression has been reported over 10 years, but there is no clear correlation between prognosis and recurrence rate. The present study evaluates prognostic implication of HER-2/neu expression. Subjects and Methods: In this study, 100 formalin-fixed paraffin-embedded specimens of primary transitional cell carcinoma of the bladder were processed. HER-2/neu monoclonal antibody immunohistochemistry staining procedure used for the study. Results: A total of 70 (70%) patients were positive for overexpression of HER-2/neu. HER-2/neu was positive in patients with 42 (70%) superficial tumor, 28 (70%) muscle invasive tumor, 41 (75.9%) high-grade tumor, 29 (63%) low grade tumor, 31 (68.9%) recurrent tumor, and 6 (66.6%) had positive lymph nodes. Conclusions: Human epidermal growth factor receptor 2/neu over expression was not correlated with the tumor stage, lymphnode metastasis or recurrence of the disease. HER-2/neu overexpression was statistically insignificantly correlated with the differentiation grade (P < 0.161) as compared to previous studies. Future studies on HER-2 expression with chemo-sensitivity and efficacy of HER-2-targeted therapies in urothelial carcinomas is needed.